肺移植治疗肺癌1例报告并文献复习 (Zhongguo Fei Ai Za Zhi, 2011)
BACKGROUND AND OBJECTIVE: Lung carcinoma is a relative contraindication for lung transplantation (LTx). The improvement of this procedure may successfully treat novel end-stage pulmonary diseases. In the present study, we reported one case of bilateral LTx (BLT) in a young man with bilateral lung carcinoma and reviewed related literature to investigate patient selection and curative effect. METHODS: A 42-year-old male patient underwent BLT on October 21, 2010 in our hospital. Preoperative chest CT and PET-CT showed bilateral multiple nodules and mass without positive lymph nodes or extrapulmonary metastasis. Bronchioloalveolar carcinoma was identifed histologically (T4N0M0, stage Ⅲb). RESULTS: Routine therapies were performed postoperatively. The patient was discharged on post-operative day 66. Tere was no clinical or radiologic evidence of the recurrence of lung carcinoma in his latest follow-up of 6 months postoperatively. CONCLUSION: LTx may be proposed as an efcient therapeutic option in selected patients of lung carcinoma.